OsBBX11 on qSTS4 links to salt tolerance at the seeding stage in Oryza sativa L. ssp. Japonica - Lei, Lei; Cao, Liangzi; Ding, Guohua; Zhou, Jinsong; Luo, Yu; Bai, Liangming; Xia, Tianshu; Chen, Lei; Wang, Jiangxu; Liu, Kai; Lei, Qingjun; Xie, Tingting; et al. (Frontiers in Plant Science, 2023)
Rice has been reported to be highly sensitive to salt stress at the seedling stage. In addition, the lack of target genes that can be used for improving salt tolerance has resulted in several saline soils unsuitable for cultivation and planting. We used 1,002 F2:3 populations derived from Teng-Xi144 and Long-Dao19 crosses as the phenotypic source to systematically characterize seedlings' survival days and ion concentration under salt stress. The QTL-seq resequencing technique and high-density linkage mapping carrying 4,326 SNP markers revealed qSTS4 as the major QTL contributing to seedling salt tolerance. Moreover, qSTS4 accounted for 33.14% of the phenotypic variation. Functional annotation, variation analysis, and qRT-PCR analysis of DNA sequences within the 46.9 Kb of qSTS4 revealed OsBBX11 as the highly likely candidate gene. Next, we generated transgenic plants using knockout-based technology and demonstrated that Na+ and K+ in the roots of the functional-loss-type OsBBX11 were translocated largely to the leaves under 120 mmol/L NaCl compared with the wild-type, causing osbbx11 leaves to die after 12 days of salt stress due to an imbalance in osmotic pressure. This finding suggested that OsBBX11 functions as a positive regulator of salt tolerance in rice seedlings. In all, this study identifies key salt-tolerance genes and SNPs in the OsBBX11 promoter region that can be used to develop salt-tolerant rice varieties.